AB0801 Evaluation of effectivity of radiotherapy for pain control in osteoarthritis and soft tissue pathology. (15th June 2017) - Aramburu, F; Montero, Ά; Silvia, R; González, J; Calvo, E; Valero, M; Rubio, C; Garcia, P de la Peña; ,
Abstract : Background: Osteoarthritis and soft tissue pathology are diseases that produce important pain and disability in many patients. Some studies support that the low-dose radiotherapy may be effective in refractory diseases. Objectives: The main objective of this study is to evaluate whether the treatment with radiotherapy is long-term effective to reduce the pain in osteoarthritis and soft tissue pathology. The secondary objective is to evaluate the analgesic requirements before and after the treatment. Methods: A prospective and observational study was designed. 38 patients were included. 53 different pathologies were treated including knee osteoarthritis, trochanteric bursitis, calcinosis, rizartrosis, pyramidal syndrome, rotatory cuff pathology and shoulder osteoarthritis, plantar fasciitis, epicondylitis, hand osteoarthritis, tibialis posterior tendonitis, ankle osteoarthritis, hip osteoarthritis and hand tendonitis. All these pathologies did not respond to conventional therapy (non steroidal antiinflamatory drugs, rehabilitation or infiltrations). Initially, the patients received a treatment of radiotherapy with a dose of 6 Gray divided in 6 sessions during 2 weeks. The patients that did not respond after 6 weeks received a second treatment with the same characteristics. The modification in Visual Analogic Scale (VAS) of pain was evaluated as well as analgesic intake before and after the treatment. Results: No side effects were observed. 92% were women and 8% men. Mean age was 66, 82, standard deviation (SD): 12, 97 (42–89). 44 locations responded to one treatment and 19 needed a second one. The mean VAS prior treatment was 7, 38, SD: 1, 49, (10–4). Mean VAS after the first treatment was 3, 81 SD: 2, 84 (9–0). The mean VAS after the first treatment in locations that received 2 treatments was 6, 65 SD: 1, 46 (9–5), and mean VAS after the second one was 4, 56 DE: 2, 66 (8–1). By pathology, the difference in means was: 4, 8 in knee osteoarthritis (N=11), 4, 78 in trochanteric bursitis (N=10), 5 in calcinosis (N=3), 5, 33 rizartrosis (N=8), 4 in pyramidal syndrome (N=2), 3, 87 in rotatory cuff pathology and shoulder osteoarthritis (N=6), 6 in plantar fasciitis (N=1), 7 in epicondylitis (N=1), 3, 22 in hand osteoarthritis (N=11), 6 in tibialis posterior tendonitis (N=2), 4 in ankle osteoarthritis (N=2), 2 in hip osteoarthritis (N=1) and 2, 2 in hand tendonitis (N=5). Until November 2016, 12 patients (17 pathologies) were followed-up for 6 months. The mean VAS before treatment of these pathologies was 7, 29 SD: 1, 21; (9–4). After 6 months mean VAS reduced to 1, 47 SD: 1, 42; (5–0). The analgesic intake was reduced in 37, 98% of patients, 10, 34% used the same amount and 34, 48% was not known. 17, 24% did not take analgesic drugs at all after treatment. Conclusions: The treatment with low dose radiotherapy was long-term effective for reducing the pain level in our study. References: Minten MJ, Mahler E, den Broeder AA et al. The efficacy and safety of low-dose radiotherapy on pain and functioning in patients with osteoarthritis: a systematic review. Rheumatol Int. 2016 Jan; 36(1):133–42. Disclosure of Interest: None declared